Catalytic Features and Thermal Adaptation Mechanisms of a Deep Sea Bacterial Cutinase-Type Poly(Ethylene Terephthalate) Hydrolase - Liu, Yu; Liu, Chen; Liu, Huan; Zeng, Qi; Tian, Xinpeng; Long, Lijuan; Yang, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
Poly (ethylene terephthalate) (PET) plastic is chemically inert and persistent. Massive quantities of PET waste end up in landfill sites and oceans, posing major global pollution concerns. PET degrading enzymes with high efficiency provide plastic recycling and bioremediation possibilities. Here, we report a novel cutinase, MtCut with distinct catalytic behaviors, derived from the deep sea Nocardiopsaceae family strain. Biochemical analyses showed MtCut efficiently hydrolyzed PET at ambient temperatures and in an exo-type manner. The activity and stability of MtCut were enhanced by the addition of calcium ions. Notably, no hydrolysis products inhibition was observed during PET depolymerization, suggesting MtCut is a better biocatalyst when compared to other PET hydrolases. In addition, structural components associated with thermal adaptation were investigated using molecular dynamic (MD) simulations, and key regions regulating MtCut thermostability were identified. Our biochemical and structural analyses of MtCut deepen the understanding of PET hydrolysis by cutinases, and provide invaluable insights on improvement and performance engineering strategies for PET-degrading biocatalysts.